Analysis of Correlation Between Vertebral Endplate Change and Lumbar Disc Degeneration - Xiao, Long (Med Sci Monit, 2017)
BACKGROUND: To evaluate the correlation between vertebral endplate change and the level of lumbar disc degeneration via magnetic resonance imaging (MRI). MATERIAL/METHODS: A total of 345 patients who were recruited from our hospital from May 2012 to May 2016 were evaluated for the presence of intervertebral disc degeneration or herniation. The degree of degeneration was assessed according to Pfirrmann grade. Vertebral endplate change was evaluated based on the endplate concave angle (ECA), and Modic change on sagittal MRI. The correlation between ECA and lumbar disc degeneration or Modic change and lumbar disc degeneration was analyzed. RESULTS: The results showed that there was no statistically significant difference in comparison of the ECAs in adjacent L3–5 vertebra between males and females. With the aggravation in degenerative changes of L3–5 discs, the ECAs of adjacent L3 superior endplate, L4 inferior and superior endplates and L5 inferior endplate were gradually enlarged, indicating the positive correlation between the lumbar disc degeneration and ECAs. The rate of Modic change in females was higher than that in males without a statistically significant difference. Area of Modic change was positively correlated with the degree of lumbar disc degeneration. Additionally, we also identified the positive correlation between the rate of Modic change and the degree of lumbar disc degeneration. CONCLUSIONS: Endplate angle and lumbar disc degeneration are positively correlated. The endplates and endplate signal changes can reflect the degree of disc degeneration and Modic changes can reflect the rate of clinical lumbar disc degeneration degree.